The Tale of Tom Kitten - Potter, Beatrix (Penguin Group, 1996)
This original, authorised version has been lovingly recreated electronically for the first time, with reproductions of Potter's unmistakeable artwork optimised for use on colour devices such as the iPad. The Tale of Tom Kitten is set in the cottage garden Beatrix created herself at Hill Top, the farm she owned near the village of Sawrey. Tom and his sisters look so smart in their new clothes. When their mother sends them outside while she waits for her visitors, she couldn't possibly guess what kind of mess they are going to get themselves into.
Keywords: Concepts